Bifunctional N-Heterocyclic Carbenes Derived from l-Pyroglutamic Acid and Their Applications in Enantioselective Organocatalysis - Chen, Xiang-Yu; Gao, Zhong-Hua; Ye, Song (Accounts of chemical research, 2020)
In nature, enzymes are a powerful medium for the construction of enantiomerically pure chemicals, which always inspires synthetic chemists to explore new catalysts to imitate the enzyme machinery for asymmetric transformations. Vitamin B1, a bifunctional thiazolium N-heterocyclic carbene (NHC) precursor, is the coenzyme for transketolase. In the past two decades, a series of chiral NHCs, including monocyclic, bicyclic, tetracyclic, and even bridged ones, have been synthesized and successfully utilized as efficient organocatalysts for a wide variety of asymmetric organic reactions. The utility of bifunctional catalysts can enhance catalytic activity and improve stereochemical control through their synchronous activation of both reaction partners. However, the NHCs possessing multiple activation sites are far less developed.This Account gives an overview of our research on the design, development, and applications of bifunctional NHCs in organocatalysis. We synthesized a series of l-pyroglutamic acid-derived bifunctional NHCs bearing a free hydroxyl group which can interact with carbonyl or imino groups via hydrogen-bonding. Further studies revealed that these bifunctional catalysts worked well for a variety of reactions. We have developed bifunctional NHC-catalyzed aza-benzoin reactions, [2 + 2], [2 + 3], and [2 + 4] cycloadditions of ketenes, [3 + 2] and [3 + 4] annulations of enals, and aza-MBH and Rauhut-Currier reactions of Michael acceptors. In addition to these reactions via nucleophilic Breslow intermediates, enolates, homoenolates, and zwitterionic azolium intermediates, the bifunctional NHC-catalyzed [3 + 3] annulation via 1,3-biselectrophilic α,β-unsaturated acyl azolium intermediates was also developed.In these reactions, bifunctional NHCs showed amazing effects compared to normal nonbifunctional NHCs. In some cases, the bifunctional NHCs facilitated reactions which did not work under normal NHC catalysis, possibly due to additional activation via H-bonding. More interestingly, the bifunctional NHCs could not only improve but also switch the enantioselectivity to get products with opposite stereochemistry through H-bond controlled stereochemical directing. Furthermore, the reaction mode could be totally changed from [3 + 2] to [3 + 4] annulation to give kinetically favored products when bifunctional NHCs were employed. In future, the applications of bifunctional NHCs in other challenging reactions, such as asymmetric reactions with carbon-carbon unsaturated bonds, and the reactions involving alkyl or heteroatom radicals will be the major focus in our group.